ANALISIS PERILAKU PENCEGAHAN DAN PENGENDALIAN HIPERTENSI DI KOTA BUKITTINGGI - Abdi Iswahyudi Yasril; Khairul Abbas (Jurnal Endurance, 2023)
Hypertension is high blood pressure in the arteries causing an increased risk of cardiovascular-related diseases. According to Riskesdas data in 2018, the prevalence of hypertension was 25.8%, in West Sumatra Province hypertension was ranked third with 248,964 cases (13.8%). The purpose of this study was to see the optimization of the implementation of hypertension prevention and control in the community to be able to identify the prevalence of hypertension in the city of Bukittinggi. This study uses a descriptive analytical research design with a cross sectional approach. The tests used are the Chi - Square test and the Multiple Logistics Regression Test. This research was conducted in all Puskesmas in Bukittinggi City. The results showed that there was a relationship between age (p = 0.002; OR = 2.493), education (p = 0.008; OR = 2.240), occupation (p = 0.031; OR = 2.129), income (p = 0.040; OR = 1.860) with hypertension prevention. Then there is no relationship between gender (p = 0.786), knowledge (p = 0.915), attitude (p = 0.540) with hypertension prevention. Based on the multivariate analysis table, there are factors that most influence the incidence of hypertension are education (p value 0.002), occupation (p value 0.039), income (p value 0.075), age (p value 0.000). Based on these results, it is expected that the role of health workers is to be able to provide education to patients in the age group of productive workers and at risk of hypertension about hypertension prevention measures in order to increase compliance in health checks so that blood pressure is in normal conditions and avoids other cardiovascular diseases due to complications of hypertension